Is Acheulean Handaxe Shape the Result of Imposed 'Mental Templates' or Emergent in Manufacture? Dissolving the Dichotomy through Exploring 'Communities of Practice' at Boxgrove, UK. Issue 4 (November 2021) - Hutchence, Laurie; Scott, Christopher
Abstract : This paper examines the debate over whether Acheulean handaxe shape results from the intentional imposition of a priorly held mental template upon the lithic material substrate or, alternatively, whether a knapper's intentions related to shape 'emerge' through the engagement (in action) of human agency and material affordances. We suggest that imposition of form and emergence of form are not mutually exclusive, and use Lave and Wenger's concept of 'communities of practice' to knit these opposed views together to explain the consolidation of homogenous handaxe shape at Boxgrove, c . 500, 000 years ago. Here we propose that the consistency in handaxe shape found at sites like Boxgrove is a consequence of the emergent actions of individual knappers being simultaneously constrained by the imposition of social norms. Social norms are referred to in action and are negotiated, understood, and adhered to at the wider group level. Therefore, we propose that contextualizing Acheulean handaxe manufacture within its wider social context will show that handaxe shape was both imposed and emergent, not one or the other.